Perancangan Sistem Kompensasi Berdasarkan Metode Tumpang Tindih (Overlapping) pada Ukm Xyz - Boya Dwilingga Ramdaniar; Dennisa Nasyavini Putri; Lindawati Kartika; Naufal Fahar Muhammad; Nazwa Nurshadrina; Sisca Marisa (Syntax Idea)
Microsoft Office Translator This study aims to analyze the compensation system in XYZ SMEs based on overlapping methods. The research method used is to collect data through interviews, observation, and documentation. The results showed that XYZ SME entrepreneurs still use an improper compensation system. As a result, the compensation received by workers is not proportional to the performance already produced. The compensation system used by XYZ SMEs is an overlapping method with several performance appraisal indicators. However, there are some shortcomings to this system such as lack of flexibility in assessing the performance of employees who have different duties and responsibilities. This study also analyzed overlapping methods for compensation systems in XYZ SMEs. This method can provide a more comprehensive and holistic picture of performance to employees. From the results of the analysis, it can be concluded that adjustments need to be made so that the compensation system in XYZ SMEs can better suit the needs and characteristics of employees and organizations